Experimental study of the effect of shoes on particle resuspension from indoor flooring materials. (June 2017) - Lai, Alvin C.K.; Tian, Yilin; Tsoi, Judy Y.L.; Ferro, Andrea R.
Abstract: Walking-induced resuspension is known to be a source of indoor particulate matter. The goal of this study is to investigate the effects of shoe type and shoe groove pattern on particle resuspension. This study is the first to investigate the shoe effect experimentally. The experiments were conducted in a controlled environmental chamber and a human participant performed prescribed stomping activity. Flooring samples were seeded with Ultrafine Arizona Test Dust prior to each experiment. Two shoe types, three groove patterns for the same shoe type, and two flooring types were tested. Resuspension fractions were estimated using a two-compartment mass balance model and normalized by contact area of the shoe with the flooring. Stomping-induced air velocity was measured at 6 locations along the edge of the shoe. Flat shoes enhanced particle resuspension fractions per contact area compared with high heels on tile, while no difference between the shoe types was observed on carpet. The no groove shoe was associated with higher resuspension fractions than grooved shoes for both flooring materials tested. Resuspension fractions, which increased with particle size, were found to be within the range of previous studies. Highlights: Effects of shoe type and shoe groove pattern on particle resuspension were studied. Stomping-induced air velocity was measured along the edge of the shoe. Flat shoes enhanced particle resuspension compared with high heels on tile. The no groove shoe was associated with higher resuspension than grooved shoes.